Tornar-se leitora: percursos de professoras - Lusa, Diana (My University, 2024)
This Doctoral research, affiliated with the Reading and Literature Observatory Research Group (OLLI) and the Educational Processes, Language, Technology and Inclusion Research Line at the Universidade of Caxias do Sul (UCS), engaged in a dialog with women, art, and Portuguese language teachers as well as teachers from the initial grades of Elementary School in São Domingos do Sul, a municipality located in the state of Rio Grande do Sul (RS), Brazil, in order to delve into their reading and writing stories and the mediation processes experienced by them, as well as those occurring in their teaching practices. Thus, the main objective of the study was: to investigate, based on the reading stories of women teachers from São Domingos do Sul – RS, their reading paths, in order to contribute to discussions about women’s reading education in Brazil and their relationship with cultural mediation. The specific objectives were: a) to learn, based on the analysis of the training path of a group of teachers from São Domingos do Sul, about their reading and writing stories; b) to understand the conditions of the woman-teachers in her training path and the gender crossings in each one; c) to identify the mediation processes in each path – those experienced and those reflected in her practices. The methodology employed in this Doctoral dissertation involved semi-structured interviews with narrative openings, conducted with empirical interlocutors, which were later transcribed, forming the corpus of the research. The narratives underwent analysis using Discursive Textual Analysis (DTA) based on Moraes and Galiazzi (2016), which resulted, at the end of data processing, in four categories. Within these categories, which were addressed in the fourth and fifth chapters of this Doctoral dissertation, the following topics were covered: what involved the choice of being a teacher for the local interlocutors; the books – physical book, living book, affection-book; the act of reading; the school’s relationship with reading and writing; the experiences of cultural mediation and reading mediation. In addition to these chapters and the first and sixth, which respectively present the introduction and final considerations, this Doctoral dissertation also consists of a theoretical chapter – the second –, which supports the study, developing the following subjects: gender and intersectionality concepts, relating them to the women’s daily lives; a brief historical path of women's encounter with reading, with the possibility of studying and with the teaching profession; conceptualization of reading and search to understand the multiple possible readings; discussion about the act of reading and thinking about literature as a fundamental human right; presentation of the concept of experience and reading experience; and, finally, reflection on the concepts of cultural mediation, reading mediation and aesthetic education. To this end, the following authors were referenced: Barthes (2013), Beauvoir (2019b), Candido (2004), Gattai (2009), Gebara (2000), Heidegger (2003), Horellou-Lafarge and Sergé (2010), Jouve (2002), Larrosa (2019), Louro (1997, 2018), Lyons (1999), Manguel (1997, 2009), Pennac (1993), Petit (2013, 2019), Scott (1995), Woolf (2014) and Yunes (2002, 2003, 2021). The third chapter provides a contextualization of the place where the research was carried out. The findings reveal the different training paths of the teachers, which have points of intersection, one of them being the centrality of the school in the life of each interlocutor – the school was the place of contact with books (physical book and, in many cases, with the affection-book and with the living-book). The unforgettable books read in childhood and adolescence are kept in a special place in each teacher’s memory. The research also shed light on the notable individuals, cultural and reading mediators present in the lives of each of the interlocutors and the ways in which they were and are themselves mediators. The study also highlighted the readings, in the plural, that emerged from the narratives and sought to discuss theoretically and empirically about experiences of literary readings. Becoming – a reader, a woman, a professional, a citizen, a mother, among others – permeated each story, being individual and collective, being part of life while there is life to live, transform, while there is a path to walk. [resumo fornecido pelo autor]
Esta pesquisa de Doutorado, vinculada ao Grupo de Pesquisa Observatório de Leitura e Literatura (OLLI) e à Linha de Pesquisa Processos Educacionais, Linguagem, Tecnologia e Inclusão da Universidade de Caxias do Sul (UCS), realizou uma interlocução com mulheres, professoras de arte e de língua portuguesa e professoras dos anos iniciais do Ensino Fundamental de São Domingos do Sul, município localizado no Rio Grande do Sul (RS), com o fim de conhecer suas histórias de leitura e de escrita e os processos de mediação vividos por elas, assim como os que acontecem em suas práticas docentes. Assim sendo, o estudo teve como objetivo geral: Investigar, a partir de histórias de leitura de mulheres professoras de São Domingos do Sul – RS, seus percursos de leitura, a fim de contribuir para as discussões acerca da formação leitora de mulheres no Brasil e sua relação com a mediação cultural. Os objetivos específicos foram: a) conhecer, a partir da análise do percurso formativo de um grupo de professoras de São Domingos do Sul, as suas histórias de leitura e de escrita; b) compreender as condições da mulher-professora em seu percurso formativo e os atravessamentos de gênero em cada caminho; c) identificar os processos de mediação em cada percurso – os vividos e os que se espelham nas práticas. A metodologia ancora-se na pesquisa qualitativa e a investigação efetiva-se a partir de entrevistas semiestruturadas com aberturas narrativas, realizadas com as interlocutoras empíricas, que foram posteriormente transcritas, sendo o corpus da pesquisa. As narrativas foram analisadas por meio da Análise Textual Discursiva (ATD) com base em Moraes e Galiazzi (2016), o que resultou, ao final da análise dos dados, em quatro categorias. Dentro dessas categorias, que foram tratadas nos capítulos quarto e quinto desta tese, os seguintes temas foram abordados: o que envolveu a escolha de ser professora das interlocutoras do local; os livros – físicos, vivos, livro-afeto; o ato de ler; a relação da escola com a leitura e a escrita; as experiências de mediação cultural e de mediação de leitura. Além desses capítulos e do primeiro e do sexto, os quais apresentam, respectivamente, a introdução e as considerações finais, esta tese ainda é composta por um capítulo teórico – o segundo –, que embasa o estudo, desenvolvendo os seguintes assuntos: conceito de gênero; breve percurso histórico do encontro das mulheres com a leitura; conceituação de leitura e discussão sobre as múltiplas leituras possíveis, sobre o ato de ler e sobre a literatura como direito fundamental do ser humano; apresentação do conceito de experiência e de experiência de leitura; e, por fim, reflexão sobre os conceitos de mediação cultural, mediação de leitura e educação estética. Para tanto, os seguintes autores foram referenciados: Barthes (2013), Beauvoir (2019b), Candido (2004), Gattai (2009), Gebara (2000), Heidegger (2003), Horellou-Lafarge e Sergé (2010), Jouve (2002), Larrosa (2019), Louro (1997, 2018), Lyons (1999), Manguel (1997, 2009), Pennac (1993), Petit (2013, 2019), Scott (1995), Woolf (2014) e Yunes (2002, 2003, 2021). O terceiro capítulo apresenta uma contextualização do local onde a pesquisa foi realizada. Os resultados da pesquisa mostram os distintos percursos formativos das professoras, os quais têm pontos de intersecção, sendo um deles a centralidade da escola na vida de cada interlocutora – a escola foi o local de contato com os livros (livro físico e, em muitos casos, com o livro-afeto e com o livro-vivo). Os inesquecíveis livros lidos na infância e na adolescência estão guardados em local especial da memória de cada professora. A pesquisa deu luz também às figuras marcantes, mediadores culturais e de leitura presentes na vida de cada uma das interlocutoras e às formas como foram e são elas mesmas mediadoras. O estudo mostrou, ainda, as leituras, no plural, que emergiram das narrativas e buscou discutir teórica e empiricamente sobre vivências e experiências de leituras literárias. O tornar-se – leitora, mulher, profissional, cidadã, mãe, entre outros – perpassou cada história, sendo individual e coletiva. O tornar-se fez e faz parte da vida enquanto há vida para viver, transformar, enquanto há caminho para andar. O tornar-se leitora, que teve atenção especial nesta pesquisa, favoreceu o tornar-se mediadora. [resumo fornecido pelo autor]
Keywords: Histórias da leitura; Mulheres leitoras; Professoras; São Domingos do Sul; Mediação cultural; Mediação de leitura; Reading stories; Women readers; Teachers; São Domingos do Sul; Cultural mediation; Reading mediation